Bacterial degradation of fossil fuel waste in aqueous and solid media - Edeki, Oghenekume Gerald (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
The generation of environmental pollutants worldwide is mainly due to over reliance on fossil fuels as a source of energy. As a result of the negative impacts of these pollutants on the health of humans, animals, plants and microorganisms, global attention has been directed towards ways of containing this problem. Biodegradation of fossil fuel is one of the most effective methods used to remediate contaminated systems. However with regard to coal waste, much of what is known is based on the ability of fungal species to biosolubilize this material under enrichment conditions in a laboratory setting. For effective biodegradation as a remediation technique, there is an immediate need to source, isolate, enrich and incorporate other microorganisms such as bacteria into bioremediation technologies. The goal of this dissertation was to isolate bacteria from fossil fuel contaminated environments and to demonstrate competence for petroleum hydrocarbon degradation which was achieved using a combination of analytical methods such as spectrophotometry, FT-IR, SEM and GC-MS. Screening for biodegradation of coal and petroleum hydrocarbon waste resulted in the isolation of 75 bacterial strains of which 15 showed good potential for use in developing remedial biotechnologies. Spectrophotometric analysis of bacteria both in coal and petroleum hydrocarbons (all in aqueous media) revealed a high proliferation of bacteria in these media suggesting that these microbes can effectively utilize the various substrates as a source of carbon. The isolated bacteria effectively degraded and converted waste coal to humic and fulvic acids; products required to enrich coal mine dumps to support re-vegetation. Scanning electron microscopy showed the attachment of bacteria to waste coal surfaces and the disintegration of coal structures while FT-IR analysis of extracted humic-like substances from biodegraded waste coal revealed these to have the same functional groups as commercial humic acid. Specific consortia which were established using the isolated bacterial strains, showed greater potential to biodegrade coal than did individual isolates. This was evident in experiments carried out on coal and hydrocarbons where the efficient colonization and utilization of these substrates by each bacterial consortium was observed due to the effect of added nutrients such as algae. The biodegradation of liquid petroleum hydrocarbons (diesel and BTEX) was also achieved using the 15 bacterial isolates. GC-MS analysis of extracted residual PHC from aqueous and solid media revealed rapid breakdown of these contaminants by bacteria. Different bacterial consortia established from the individual isolates were shown to be more efficient than single isolates indicating that formulated consortia are the biocatalysts of choice for fossil fuel biodegradation. This study represents one of the most detailed screenings for bacteria from fossil fuel contaminated sites and the isolation of strains with potential to biodegrade coal and petroleum hydrocarbon wastes. Several consortia have been developed and these show potential for further development as biocatalysts for use in bioremediation technology development. An evaluation of efficiency of each established bacterial consortium for biodegradation in a commercial and/or industrial setting at pilot scale is now needed.
Keywords: Uncatalogued